The Influence of Halal Label and Brand Image on Purchase Decisions of Local Skincare Products with Price as a Moderating Variable (Case Study on Wardah) - Titania Aulia Wahyuni; Irfan Syauqi Beik; Mimin Aminah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of halal labeling and brand image on purchase decisions of local skincare products, with price as a moderating variable. In recent years, the halal cosmetics industry in Indonesia has experienced rapid growth, driven by increasing awareness among Muslim consumers regarding the importance of halal-certified products. Wardah, as a pioneering local halal cosmetic brand, serves as a compelling case study due to its success in combining religious values with modern marketing strategies. This research adopts a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS), involving 190 respondents aged 15–45 who have previously used Wardah products. The results reveal that brand image and price significantly influence purchase decisions, whereas halal labeling does not have a direct significant impact. Interestingly, price is found to strengthen the effect of brand image on purchase decisions but weaken the effect of halal labeling. These findings suggest that in the context of modern consumers particularly younger generations perceived value and brand positioning play a more dominant role than religious certification alone. Therefore, companies need to develop a balanced strategy that emphasizes strong brand identity, competitive pricing, and effective communication to reinforce the appeal of halal products in the market.